2021
DOI: 10.3389/fgene.2021.738485
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Genetic and Socioenvironmental Contributions to Ethnic Differences in C-Reactive Protein

Abstract: C-reactive protein (CRP) is a routinely measured blood biomarker for inflammation. Elevated levels of circulating CRP are associated with response to infection, risk for a number of complex common diseases, and psychosocial stress. The objective of this study was to compare the contributions of genetic ancestry, socioenvironmental factors, and inflammation-related health conditions to ethnic differences in C-reactive protein levels. We used multivariable regression to compare CRP blood serum levels between Bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A growing number of multilevel studies have examined African ancestry as a predictor of chronic disease endpoints [ 20 , 21 , 36 , 46 , 63 67 ]. Geographic analyses of migration patterns in the US have shown that genetic admixture patterns in present-day African Americans are associated with forced movements of people that occurred during the trans-Atlantic slave trade [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing number of multilevel studies have examined African ancestry as a predictor of chronic disease endpoints [ 20 , 21 , 36 , 46 , 63 67 ]. Geographic analyses of migration patterns in the US have shown that genetic admixture patterns in present-day African Americans are associated with forced movements of people that occurred during the trans-Atlantic slave trade [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…When adopting a social sciences theory of health disparities, scientists estimating causal effects of genetic ancestry on health outcomes should control for variables assumed to be consequences of historical systematic racism, discrimination, and segregation to avoid conflating genetic ancestry effects with these other correlates of SIRE. A growing number of multilevel studies have examined African ancestry as a predictor of chronic disease endpoints [20,21,36,46,[63][64][65][66][67]. Geographic analyses of migration patterns in the US have shown that genetic admixture patterns in present-day African Americans are associated with forced movements of people that occurred during the trans-Atlantic slave trade [23,24].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…revealed higher serum levels of inflammation-mediated C-reactive protein (CRP) in UK populations composed largely of older, Black females. Notably, the sample included only 6,456 (0.1%) Black subjects and 426,842 (98.5%) White subjects ( 4 ). Compared to census demographics reported during the same time period (2006-2011), this sampled population underrepresents Black communities ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…UKBB participants' genome-wide genotypes were characterized using the UKBB Axiom Array or United Kingdom BiLEVE Array as previously described (23,30). UKBB participant genomewide genotypes were merged and harmonized with genomic variant data from global reference populations characterized as part of the 1KGP ( 26) and the Human Genome Diversity Project (HGDP) (31) as previously described (32,33). Reference populations were grouped into seven regional ancestry groups based on their genetic and geographic affinity.…”
Section: Uk Biobankmentioning
confidence: 99%